The Relationship between Diabetes Self-Management Education and Health-Related Quality of Life (HRQoL) among Patients with Type 2 Diabetes Mellitus - Probosiwi, Neni; Siswidiasari, Arifani (International Journal of Contemporary Sciences (IJCS), 2024)
Diabetes Mellitus (DM) is a chronic metabolic condition marked by elevated blood glucose levels, leading to damage in critical organs. This study aimed to evaluate the relationship between diabetes self-management education (DSME) and health-related quality of life (HRQoL) in type 2 diabetes patients at the Balerejo Community Health Center. A prospective cross-sectional study was conducted, collecting data from 50 patients using consecutive sampling and analyzed through the Chi-Square test. The demographic profile showed that 60% of participants were female, 60% were aged 36-45, and 56% had a normal BMI. Most patients had good dietary management (64%) but poor physical exercise habits (84%). HRQoL results indicated that 64% scored high in physical functioning, with other domains such as vitality (56%) and social functioning (56%) also showing positive outcomes. A significant relationship was found between DSME and HRQoL, with a P-value of 0.002 and an odds ratio of 7.2. These findings underscore the crucial role of DSME in enhancing the quality of life for type 2 diabetes patients by promoting better disease management practices.